Pengembangan Media Pembelajaran Puzzle Kreatif Pada Materi Membaca Permulaan Siswa Kelas I SDN 05 Salamae Kota Palopo - Nurul Mujtahidah; Yusuf, Munir; Guntur, Muhammad; Aswar, Nurul (Jurnal Konsepsi, 2023)
This thesis discusses research into the development of creative puzzle learning media in beginning reading material for class I at SDN 05 Salamae, Palopo city. This research aims to: (1) Analyze the need for creative puzzle media in beginning reading materials (2) Find out the level of validity of creative puzzle learning media in developed beginning reading materials (3) Find out the level of practicality of creative puzzle learning media in developed beginning reading materials tested. This type of research is Research and Development (R&D) research using the ADDIE development model of 5 stages, namely: analysis, design, development, implementation and evaluation stages. This research was carried out in 2023 involving 22 class I students at SDN 05 Salamae. Meanwhile, the object of the research is creative puzzle learning media which was developed according to student needs. Research data was collected through questionnaires, interviews and tests and then analyzed qualitatively and quantitatively. Based on the results of the validity of creative puzzle media which has been validated in categories, design experts get a score of 73% in the valid category. Meanwhile, linguists got a percentage score of 96% in the very valid category. The results were very satisfying and positive with the final score obtained from the practicality test results being 95.09% in the very practical category and the class I teacher with the score obtained from the practicality test results being 82% in the very practical category.